Peningkatan Performa Pelayanan Publik Melalui Penerapan Core Values BerAKHLAK di Kota Singkawang Tahun 2022-2023 - Gunawan, Gunawan; Deliarnoor, Nandang Alamsah; Yuningsih, Neneng Yani (Jayapangus Press, 2024)
In the midst of increasingly high public demands for quality public services, the government through service officers must be able to serve professionally. Implementation and apllication of the core values of BerAKHLAK is one of the main keys to realizing excellent public services. This study aims to examine the process of internalization and application of the core values of BerAKHLAK carried out in Singkawang City in the implementation of public services and their contribution to improving the performance of quality public services for the community. The research method used is a descriptive research type and qualitative approach. Informants were selected through purposive and snowball sampling techniques. Data analysis techniques included data reduction, data presentation, and conclusion/verification sourced from observation, interviews and documentation. The results showed that the internalization of the core values of BerAKHLAK in Singkawang City has been running well and has had a positive impact on improving public service performance. This is evidenced by the increasing value of the public service index in Singkawang City by the Ministry of PAN-RB with a score of 4.22 in 2022 from previously in 2021 getting a score of 3.57. In addition, public satisfaction with public services in Singkawang City has also increased as seen from the value of the public satisfaction index, and the commitment of UPP in Singkawang City to improving the quality of public services. However, there are still weaknesses in several aspects of service. Therefore, The Singkawang City Government must continue to make sustainable efforts to improve the quality of public services in Singkawang City.